Bibliometric analysis of neural injury biomarkers in neurodegenerative diseases: research trends and future perspectives - Pa, Chengzhou; Shen, Shijun; Dai, Yunrui; Wu, Min (Frontiers in Human Neuroscience, 2025)
IntroductionNeurodegenerative diseases (NDs) are progressive disorders with an increasing global health impact. Neural injury biomarkers have emerged as potential tools for early diagnosis and disease monitoring.MethodsTo map research trends in this field, we conducted a comprehensive bibliometric analysis of 1,228 peer-reviewed articles published from 1991 to 2024 using CiteSpace and the Bibliometrix R package.ResultsOur analysis revealed steady publication growth, particularly accelerating after 2015. The United States, United Kingdom, and China produced the highest volume of publications and citations, with institutions such as the University of California System and Harvard University serving as key collaboration hubs. Early research prioritized tau, amyloid-beta (Aβ), cerebrospinal fluid (CSF), and mild cognitive impairment (MCI). Since 2020, the focus has expanded to blood-based biomarkers, exosomal microRNAs, and inflammation-related markers such as glial fibrillary acidic protein (GFAP) and translocator protein (TSPO). Through citation and clustering analyses, we identified three developmental phases: (1) CSF-based amyloid/tau validation, (2) multimodal and genetic biomarker integration, and (3) the emergence of plasma and neuroinflammatory markers.DiscussionThese trends reflect a paradigm shift toward minimally invasive and multifactorial diagnostic approaches. Our findings underscore evolving priorities in NDs biomarker research and highlight the importance of multi-omics, artificial intelligence (AI), and interdisciplinary collaboration for translational discovery and clinical application.